La lussazione acuta del gomito - Giannicola, G.; Ascani, C.; Spinello, P. (Lo Scalpello - Journal, 2018)
SIMPLE ACUTE ELBOW DISLOCATIONSimple acute elbow dislocation is defined as the loss of bone congruity of the elbow following trauma, withoutassociated bone injuries. An adequate fluoroscopic evaluation of the stability after reduction is mandatory to chooseeither the conservative or the surgical treatment. Persistent joint instability or incongruency beyond 40° of flexionafter reduction or recurrence of dislocation represent the main indication for surgery. The identification andclassification of the type of ligamentous and musculotendinous lesions is fundamental to select the correct repairtechnique. Early rehabilitation is mandatory for rapid recovery of elbow function.